Capital quality improvement and the sources of growth in the euro area - Plutarchos Sakellaris; Focco Vijselaar (European Central Bank (ECB), 2004)
Capital quality improvement is a general phenomenon. Therefore quality correction is needed in price indexes. There is substantial evidence of biases in the official price indexes of capital equipment. We apply to euro area statistics estimates of these biases based on US data thus deriving quality-adjusted price indexes. Adjusted for quality, productive capital stocks of equipment and software grow on average 3 percentage points faster annually - a doubling of their growth rates. Quality-adjusted output grows 0.46 percentage points faster annually - a 20 percent increase. In terms of growth accounting, quality adjustment subtracts 11 percentage points from the share of TFP in aggregate growth and adds them to the share of equipment stock. For the 1990s only the difference is even higher: 14 percentage points. When all is told, embodied technological change accounts for 46 percent of (quality-adjusted) output growth in the euro area over the period 1982 to 2000.
Keywords: O3; O47; D24; E22; 330; embodied technological change; equipment investment; euro area; investment price deflators; output growth